TINJAUAN KESTABILAN PERKUATAN LERENG MENGGUNAKAN DINDING KANTILEVER DAN DINDING GRAVITASI - Eka Liani, Annisa; Patuti, Indriati Martha; Bahsuan, Rifadli (Composite Journal, 2021)
Parts of Gorontalo are hills and mountains close to community settlements, which are prone to landslides. To do a research on literature review that analyzes slope reinforcement models, which will be taken into consideration for slope improvement steps in Gorontalo. Slope reinforcement includes retaining walls, gravity walls, cantilever walls and crib walls. This research discusses slope reinforcement models and their stability behavior analysis. Secondary data is in the form of research journals on slope reinforcement models. Calculation data that will be used as experimental data for modeling other retrofitting walls are obtained from the results of research from one of the reviewed journals, namely multilevel gravity walls. The wall that will be analyzed is the retaining wall of a multilevel cantilever type of wall. Analysis of active soil pressure using the Rankine method and slope stability analysis using the slice method which is carried out with the help of 2D Slide software. Based on the results of the stability analysis of slope reinforcement with the selection of stratified cantilever wall reinforcement, the value of the safety factor against sliding (Fgs) is 1.63>1.5, the safety factor against overturning (Fgl) is 2.44>2.0, the safety factor against the collapse of carrying capacity (F) is 8.49>3.0, and the global safety factor value is 1.56>1.5. The value of the safety factor for shifting and rolling has decreased by 1% and 20% respectively compared to the gravitational wall. In the wall bearing capacity, there was an increase of 31%. Changes that occur in the safety factor in cantilevered walls are caused by changing factors in the dimensions of the walls which affect the strength of the structure in the soil holding force and the type of working principle of the walls. As for the global slope stability analyzed, there was a decrease in the safety factor by 5% after changing the type of reinforcement, but it showed that the slope was still stable, because the cantilevered wall type has a slender front wall dimension compared to the gravity wall which is more resistant to the risk of lateral slope movement.